MODEL PEMBERDAYAAN MASYARAKAT TERHADAP PERENCANAAN PEMBANGUNAN DESA CARAWALI - Hasmawati Hasmawati; Hariyanti Hamid; Kamaruddin Sellang (JIA: Jurnal Ilmiah Administrasi, 2021)
The purpose of the study was to determine the community empowerment model for the implementation of development planning in carawali village, to find out whot factors were supporting and inhibiting community empowerment in the implementation of development planning in carawali villagr. The population of this study was 644 families, while the research sample was 87 families. Data collection techniques used in the study were observation, questionnaires and literature study, while the data analysis technique used was likert-scale data analysis. The collected data is then analyzed using a frequency table and using the SPSS application. The result of the research on community empowerment models for development planning in Carawali village, Wattang Pulu district, Sidenreng Rappang regency with an average value of 74,75% in the good category. The supporting factors for community empowerment on development planning in Carawali Village, Watang Pulu dictrict sidenreng rappang regency with a percentage of 57% while the inhibiting factors for community empowerment on development planning in Carawali Village, Wattang pulu district with a percentage of 49,4.